Design of a concurrent tri-band LNA based on composite right/left-handed transmission line resonators - Faycal El Hardouzi; Mohammed Lahsaini; Mustapha Bahich; Badr Nasiri; Younes Achaoui (Universitas Ahmad Dahlan, 2025)
This article presents a three-band low noise amplifier (LNA) in microstrip technology based on composite right left handed transmmision line (CRLH TL) resonators for multi-band behavior, which has been designed to meet all the criteria that determine the quality of its operation. The transistor used is biased via a transmission line and matched by λ/4 transformer filters with CRLH-TL type resonators at the output to establish multiband behavior with improved band rejection to suppress unwanted frequencies and interference. The results demonstrate excellent performance at three frequencies: 900 MHz (15.03 dB gain), 2.1 GHz (13.58 dB gain), and 3.5 GHz (12.57 dB gain), with a noise figure below 2 dB and unconditional stability. The size of the proposed amplifier is 73×63 ??2 in area.